Online platform algorithmic control and gig workers’ turnover intention in China: The mediating role of relative deprivation - Shengxian Yu; Shanshi Liu; Xiaoxiao Gong; Chang-e Liu; Wei Cai (Journal of Management Science and Engineering)
Based on the job demands-resources (JD-R) model, this study aims to investigate how algorithmic behavioral constraint and algorithmic tracking evaluation affect gig workers’ turnover intention by increasing relative deprivation and the extent to which this mediating role is moderated by algorithmic standardized guidance. Data from 242 gig workers were collected in two rounds and used to test the hypotheses. The results reveal that algorithmic behavioral constraints and algorithmic tracking evaluation are positively related to turnover intention, while algorithmic standardized guidance is negatively related to turnover intention. Moreover, algorithmic behavioral constraint and algorithmic tracking evaluation are positively related to turnover intention through relative deprivation, with algorithmic standardized guidance weakening this effect.